Cases of Situs inversus: a report - S.Bilodi, Arun Kumar; Jain, Neeraj; Sinha, B.N.; Jain, Vibha (Journal of Institute of Medicine Nepal, 1999)
SITUS INVERSUS is the mirror image of normal, where there is transposition of abdominal viscera associated with dextrocardia. It is often accidentally discovered during routine physical examination and radiological examination. In the present study, there are two cases of situs inversus. One adult male of 23 years presented with dextrocardia and situs inversus was accidentally detected during the routine physical examination. In another case, a 9-month male child also presented with situs inversus with ventricular septal defect. The above cases are found to be rare elsewhere but in Nepal it seems to be common. Hence, these cases were studied and reported.